The effect of a multicomponent training program in elderly’s body composition - Monteiro, A.M. (2019)
Physical exercise is recommended to maintain the muscular mass in elderlies (Singh, 2002). Among the different types of exercise programs, there is the multicomponent training (Carvalho et al., 2010). The multicomponent training program allows the subjects to improve their physical condition (Strength, resistance, flexibility and balance) (Carvalho et al., 2009). However, there is no consensus about the influence of multicomponent training in body composition. Thus, the aim of this study was to access the multicomponent training effect in elderly’s body composition. The sample of this study was composed of forty nine 64.39 (± 6.33) year-old elderlies. Among them, 11 were 67.45 (± 4.93) year-old males and 38 were 63.50 (± 7.47) year-old females. All procedures carried out in this research were in accordance to the Declaration of Helsinki. A multicomponent training program was applied with the Carvalho et al, (2009). The program took 8 months and the training frequency was three times per week. The elderly’s body composition were assessed with bio-impedance (Tanita, BC-545). The T-test allowed to assess the differences between the pre and post training program in the body composition. The tests were performed with a significant level of 5%. A multicomponent training program in elderlies seems to influence the body composition. The total body mass decreased between the two moments. The bone mineral mass and body water percentage had a significant increase between the two moments. Even more, all the variables improved between the two moments.